Հայկազեան համալսարանի հրատարակչատունը - Տագէսեան, Անդրանիկ (Հայկական գրադարանային ասոցիացիա)
Haigazian University Press brings an academically characteristic and unique addition to the Armenian book publishing industry in Lebanon, publishing an average of three to four books per year.
Keywords: Գրահրատարակչություն; Հայկազեան համալսարան; Հայ տպագրութեան պատմութիւն